EFEKTIFITAS IMPLEMENTASI LEARNING MANAGEMENT SYSTEM (LMS) DALAM KONTEKS MANAJEMEN PENDIDIKAN DI SMK - Ngatmini; Osberth Sinaga; Wildansyah Lubis (SCHOOL EDUCATION JOURNAL PGSD FIP UNIMED, 2025)
This study aims to analyze the effectiveness of Learning Management System (LMS) implementation in the context of educational management in Vocational High Schools (SMK), with a prospective study at SMK Negeri 8 Medan. The research approach uses a quantitative method design. The main variables include: the quality of LMS implementation (infrastructure, teacher training, user adoption), learning outcomes (student technical competence, achievement of competency standards), and managerial indicators (administrative efficiency, teacher performance monitoring). The sample involved students, teachers, and education personnel. The analysis used a mixed linear model for longitudinal data and thematic analysis for qualitative data. The results are expected to provide empirical evidence on the determinants of LMS effectiveness and managerial recommendations for optimizing implementation in SMK.